Vicarious Liability and the Intensity Principle - Urs Schweizer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
The present paper provides an economic analysis of vicarious liability that takes information rents and monitoring costs to be borne by the principal explicitly into account. In the presence of information rents or if the principal is wealth constrained herself, vicarious liability need not generate efficient precaution incentives. Rather, precaution incentives turn out to depend on the exact quantum of damages specified by courts. I shall compare incentives under three damages regimes: strict liability, the traditional negligence rule, and proportional liability. To do so, I make use of the intensity principle that allows to rank damages regimes based on the monotonicity of differences of the principal's expected payof f as a function of induced precaution.
urn:nbn:de:bvb:19-epub-13190-8
Keywords: K13; D62; 330; vicarious liability; precaution incentives; judgement-proof principals and agents; discrepancy between private and social costs; Haftung; Prinzipal-Agent-Theorie; Ökonomischer Anreiz; Umweltvorsorge; Kosten; Externer Effekt; Theorie